Aging and education: impressions from the educational workshop/Aging and education: impressions from the educational workshop - Edja Souza Barbosa; Maria Lays da Silva; Mariana Ferreira Torres de Araújo; Sara Jane Cerqueira Bezerra (Universidade Estadual de Alagoas, 2020)
This is an account of the experience of the implementation of the Aging and Education Pedagogical Workshop: weaving possible paths in the Pedagogy course of Campus III of the State University of Alagoas. The aim of the workshop was to articulate the theoretical knowledge of aging at both the medical and psychological levels, in a teacher education environment, with the goal of raising awareness of being elderly. The workshop was developed in three moments: lecture; elderly participation and aging circuit. With this experience, the authors affirm that, in view of social changes and the increase of the elderly population, pedagogy becomes a favorable science for the dialogue of actions that give visibility to the needs of this portion of the population. They also highlight the great gain of education with the amendment in LDBEN 9394/96 through Law No. 13.632/2018 that added an item in article 37, ensuring lifelong education in social daily life and in different educational spaces.